Enhancement of haemopoietic recovery in sublethally gamma-irradiated mice by the joint use of indomethacin and cystamine - Kozubík, A; Pospísil, M; Netíková, J (Folia biologica, 1990)
The effects of indomethacin and cystamine, administered prior to gamma-irradiation of mice, were investigated. Synergistic enhancement of haemopoietic recovery was observed under the conditions of a joint use of both drugs. The reason for this synergistic action is probably a joint operation of two mechanisms, i.e., the lowering of the radiosensitivity of haemopoietic stem cells by cystamine and the increase of the proliferation of surviving haemopoietic cells by indomethacin.
Keywords: velikost orgánu; Male; slezina; Organ Size; Indomethacin; mužské pohlaví; Drug Synergism; buněčné dělení; počet leukocytů; hematopoetický systém; Spleen; synergismus léků; Leukocyte Count; Animals; Cystamine; Cell Division; zvířata; Bone Marrow; Hematopoietic System; kostní dřeň; myši; cystamin; indomethacin; Mice; Radiation-Protective Agents; radioprotektivní látky